2004
DOI: 10.1128/mcb.24.23.10448-10455.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Deficiency in SNM1 Abolishes an Early Mitotic Checkpoint Induced by Spindle Stress

Abstract: Spindle poisons represent an important class of anticancer drugs that act by interfering with microtubule polymerization and dynamics and thereby induce mitotic checkpoints and apoptosis. Here we show that mammalian SNM1 functions in an early mitotic stress checkpoint that is distinct from the well-characterized spindle checkpoint that regulates the metaphase-to-anaphase transition. Specifically, we found that compared to wild-type cells, Snm1-deficient mouse embryonic fibroblasts exposed to spindle poisons ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…How any putative kinetochore or checkpoint defects in 53BP1 mutants contribute to T cell lymphomagenesis in the context of p53 deficiency remains an open question, although some clues may be emerging. 53BP1 has been reported to interact with Cdc27, a component of the anaphase-promoting complex (34). Intriguingly, the Artemis-related protein Snm1 has also been reported to associate with 53BP1 and coimmunoprecipitates with Cdc27 (31,35).…”
Section: Discussionmentioning
confidence: 99%
“…How any putative kinetochore or checkpoint defects in 53BP1 mutants contribute to T cell lymphomagenesis in the context of p53 deficiency remains an open question, although some clues may be emerging. 53BP1 has been reported to interact with Cdc27, a component of the anaphase-promoting complex (34). Intriguingly, the Artemis-related protein Snm1 has also been reported to associate with 53BP1 and coimmunoprecipitates with Cdc27 (31,35).…”
Section: Discussionmentioning
confidence: 99%
“…Higher tendency for teraploidization and for micronuclear formation is commonly reported in cells deficient in mitotic checkpoint elements, such as MAD2, Chfr and SNM1 (Scolnick and Halazonetis, 2000;Michel et al, 2001;Akhter et al, 2004) …”
Section: Nek7-negative Mefs Do Not Exhibit Metaphase Arrestmentioning
confidence: 95%
“…However, mammalian SNM1A-deficient cells exhibit no hypersensitivity to IR and only a modest hypersensitivity to interstrand cross-linking agents (Dronkert et al, 2000;Ahkter et al, 2005), although sensitivity to cisplatin has been observed in chicken DT40 cells (Ishiai et al, 2004;Nojima et al, 2005). Intriguingly, Snm1A-deficient mouse embryonic fibroblasts are highly sensitive to spindle poisons such as nocodazole and taxol, and Snm1A has been shown to be involved in an early mitotic checkpoint pathway in response to these drugs (Akhter et al, 2004). This mitotic checkpoint pathway appears to be congruent with that involving the Chfr tumor suppressor gene (Scolnick and Halazonetis, 2000;Chaturvedi et al, 2002;Matsusaka and Pines, 2004;Summers et al, 2005;Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%